Trade composition and total factor productivity: evidence for Chile - Dierk Herzer (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2005)
This paper examines the long-run impact of capital goods imports, intermediate goods imports, and exports of manufactured and primary goods on total factor productivity in Chile. Using cointegration techniques, we find productivity-enhancing effects of capital and intermediate goods imports as well as manufactured exports, and productivity-limiting effects of primary exports.
Keywords: O47; F41; C22; 330; Trade Composition; Productivity; Cointegration